Moral Education in Ibnu Jama’ah Perspective - Hendra Asla Fahmi; Yuri Ansari Panjaitan; Doni Doni; Ira Suryani; Sapri Sapri (LPPM UIKA Bogor, 2024)
The main loss is the aspect of example and instilling values that are crystallized in teaching objectives. Because the goal of directing students originates more from the teacher than from the student, even though that goal is formulated by educational staff who have a higher position in the bureaucratic structure. Students are human beings who are capable of being educated and need education in order to actualize their potential and to gain knowledge to meet life’s needs and as a provision for worshiping Allah. Therefore, it is appropriate for students before studying to equip themselves with noble morals as an effort to prepare themselves for success.. Learning Methods Ibn Jama’ah’s concept of learning methods places a lot of emphasis on memorization rather than other methods. The memorization method does not provide opportunities for the mind to make maximum use of the thinking process, however, memorization actually challenges the mind’s ability to always be active and concentrate on the knowledge gained.